Natural infection of bats with Leishmania in Ethiopia - Kassahun, Aysheshm; Sadlova, Jovana; Benda, Petr; Kostalova, Tatiana; Warburg, Alon; Hailu, Asrat; Baneth, Gad; Volf, Petr; Votypka, Jan (Acta tropica, 2015)
The leishmaniases, a group of diseases with a worldwide-distribution, are caused by different species of Leishmania parasites. Both cutaneous and visceral leishmaniasis remain important public health problems in Ethiopia. Epidemiological cycles of these protozoans involve various sand fly (Diptera: Psychodidae) vectors and mammalian hosts, including humans. In recent years, Leishmania infections in bats have been reported in the New World countries endemic to leishmaniasis. The aim of this study was to survey natural Leishmania infection in bats collected from various regions of Ethiopia. Total DNA was isolated from spleens of 163 bats belonging to 23 species and 18 genera. Leishmania infection was detected by real-time (RT) PCR targeting a kinetoplast (k) DNA and internal transcribed spacer one (ITS1) gene of the parasite. Detection was confirmed by sequencing of the PCR products. Leishmania kDNA was detected in eight (4.9%) bats; four of them had been captured in the Aba-Roba and Awash-Methara regions that are endemic for leishmaniasis, while the other four specimens originated from non-endemic localities of Metu, Bedele and Masha. Leishmania isolates from two bats were confirmed by ITS1 PCR to be Leishmania tropica and Leishmania major, isolated from two individual bats, Cardioderma cor and Nycteris hispida, respectively. These results represent the first confirmed observation of natural infection of bats with the Old World Leishmania. Hence, bats should be considered putative hosts of Leishmania spp. affecting humans with a significant role in the transmission.
Keywords: Animals; kDNA; leishmanióza kožní; Geography; kinetoplastová DNA; leishmanióza viscerální; Chiroptera; Leishmaniasis, Visceral; zeměpis; Leishmaniasis, Cutaneous; DNA, Kinetoplast; ITS1; Leishmania; Bats; Ethiopia; Etiopie; zvířata; Natural infection; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction